2018
DOI: 10.14210/alcance.v25n2(mai/ago).p126-141
|View full text |Cite
|
Sign up to set email alerts
|

The Mission as a Driver for Strategy Formulation in Higher Education Institutions

Abstract: This study aims to identify whether and how Brazilian higher education institutions (HEIs) are using organizational mission statements as drivers of strategy. Based on the effectiveness of the mission model proposed by Pearce and David (1987), this paper presents a content analysis of the mission statements of ninety-one HEIs, based on information available on their websites. The results show that philosophy, type of service, and self-concept are the most frequent elements found, and that none of the ninety-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 9 publications
(41 reference statements)
0
0
0
1
Order By: Relevance
“…The larger the word size, the greater its occurrence. Correlating this research with other studies, we observed that the words development and formation are referenced among those with the highest incidence in the study by Haberkamp, Hoppen and Diehl (2018). Observing the cloud of words prepared by the authors, even in lesser frequency, the most famous words in this study (promote, education, teaching and professional) have a proportion highlighted by their incidence.…”
Section: Hermeneutical Analysis Of the Mission Statements Of The Fede...supporting
confidence: 85%
See 3 more Smart Citations
“…The larger the word size, the greater its occurrence. Correlating this research with other studies, we observed that the words development and formation are referenced among those with the highest incidence in the study by Haberkamp, Hoppen and Diehl (2018). Observing the cloud of words prepared by the authors, even in lesser frequency, the most famous words in this study (promote, education, teaching and professional) have a proportion highlighted by their incidence.…”
Section: Hermeneutical Analysis Of the Mission Statements Of The Fede...supporting
confidence: 85%
“…We characterised the collected data as secondary data. The institutional mission statements are analysed from the perspective of the model by Pearce and David (1987) with a focus on the educational context outlined by Haberkamp, Hoppen and Diehl (2018) Based on Haberkamp, Hoppen and Diehl (2018), we included two new elements: graduates' profiles and the educational institution's contributions to the community/region. According to the authors, this addition is a reflection of the high number of words in the analysed mission statements.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…De acordo com Abelman e Dalessandro ( 2008), na maioria das IES as declarações institucionais aparecem como uma declaração da missão ou da visão, ou ambas. Para Haberkamp et al (2018), a criação da declaração da missão é a primeira parte do processo de planejamento para estabelecer prioridades e metas, todavia, quando se trata de IES, os objetivos nem sempre aparecem de maneira clara.…”
Section: Missão Visão E Valores Em Instituições De Ensino Superiorunclassified